Learning through a Foundation Degree - Taylor, Claire (2009)
This research explores the learning experiences of three mature students studying for a Foundation Degree – a two-year qualification, introduced in England and Wales in 2001, that uniquely spans the academic-vocational nexus within higher education. Data collected through interviews and journal entries were used to construct accounts of each of the students’ learning experiences, forming a longitudinal case study that spanned two years. This material is used in three ways to give insight into learning through a Foundation Degree. Firstly, the accounts stand by themselves as detailed descriptions of what it is like to learn through a Foundation Degree. Secondly, the accounts illustrate ways in which particular learning theories and models are helpful to understanding the students’ learning experiences, and also the areas in which some theories and models fall short. Thirdly, a new conceptual model has been developed which identifies six factors that significantly impact upon the Foundation Degree learner’s experience. Each of these factors has the potential to influence learning positively or negatively, depending on where it lies upon a continuum that polarises learning inhibitors and enablers. This model is used to scrutinise Foundation Degree teaching and learning practice, using the accounts as reference points, and more effective approaches to Foundation Degree delivery have been suggested.